Detection of Damage Motor and Coal Crusher in Power Plant Tanjung Enim 3 X 10 MW Using Vibration Analysis - Septano, Gurruh Dwi; Ikbal, Ikbal; Fathoni, Fathoni; Sriwijaya, Sayid Bahri; Putri, Salsanabila Mariestiara (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2024)
Motor and coal crushers are critical in coal size reduction for efficient energy production. Continuous operation often impacts their functionality, necessitating effective maintenance methods. This study employs vibration analysis to monitor the health and detect potential faults in the motor and coal crusher. Vibration values, measured under load and no-load conditions, were analyzed in vertical, horizontal, and axial directions using ISO 10816 standards. Results show that while vibration levels remained within safe limits, increased readings in specific areas, particularly at the Crusher NDE in axial direction under load conditions, suggest potential issues like misalignment or bearing wear. Prominent vibration peaks at lower frequencies in the spectrum further support these findings. This research underscores the importance of routine vibration monitoring to preemptively address machine faults, ensuring optimized operation and minimized downtime. Vibration analysis proves effective for predictive maintenance and operational reliability in coal processing systems.